In vitro gastrointestinal absorption of red wine anthocyanins – Impact of structural complexity and phase II metabolization. (1st July 2020) - Han, Fuliang; Oliveira, Hélder; Brás, Natércia F.; Fernandes, Iva; Cruz, Luís; De Freitas, Victor; Mateus, Nuno
Highlights: Red wine 3-diglucoside anthocyanins are transported through gastrointestinal cells. Phase II metabolite malvidin-3-glucuronide was transported through both cell lines. Free glucoside moieties have an important role in the absorption of anthocyanins. Abstract: Malvidin-3 -O- glucoside, malvidin-3, 5 -O- diglucoside, malvidin-3 -O- (6 -O- coumaroyl)-glucoside-5 -O- glucoside from Chinese Vitis davidii red wine were used to investigate the role of glucoside, diglucoside and coumaroylated glucoside moieties on their transport efficiency through MKN-28 gastric and Caco-2 intestinal cells. Due to the already described conversion of 3- O -glucosylated anthocyanins into 3- O -glucuronidated, the 3- O -glucuronidated metabolite of malvidin-3- O -glucoside was also tested. The antiproliferative activity was higher for the glucuronidated metabolite in both cell lines. All anthocyanins were transported through MKN-28 gastric cells and Caco-2 intestinal cells with transport efficiencies ranging from 4% to 9% in MKN-28 and from 3% to 5% in Caco-2. No significant differences on transport efficiencies were observed at 180 min among the different anthocyanins in MKN-28. The transport efficiency of malvidin-3 -O- glucuronide at 180 min was about 3–4% in Caco-2 and MKN-28 cells. Computational studies were performed to evaluate the interaction between anthocyanins and glucose gastric transporters GLUT1 and GLUT3, which supported the experimental findings.